2018
DOI: 10.1002/lary.27175
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biofilm Formation, Gram‐Negative Infections and TAS2R38 Polymorphisms in CRSw NP Patients

Abstract: 2b. Laryngoscope, 128:E339-E345, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 44 publications
5
38
0
3
Order By: Relevance
“…1 (b and c) and 2e). Together, these results suggest that several T2Rs expressed in the airway can detect bacterial quinolones, including T2R38, which has been implicated in chronic rhinosinusitis (12,23,(25)(26)(27)(28)(29)71).…”
Section: Pqs and Hhq Activate T2r-dependent Ca 2؉ Signals In A Heteromentioning
confidence: 74%
See 1 more Smart Citation
“…1 (b and c) and 2e). Together, these results suggest that several T2Rs expressed in the airway can detect bacterial quinolones, including T2R38, which has been implicated in chronic rhinosinusitis (12,23,(25)(26)(27)(28)(29)71).…”
Section: Pqs and Hhq Activate T2r-dependent Ca 2؉ Signals In A Heteromentioning
confidence: 74%
“…The relevance of T2R38 to immunity is supported by clinical data linking polymorphisms in the TAS2R38 gene to sinonasal disease (16,21). Patients homozygous for the AVI TAS2R38 polymorphism, which results in nonfunctional T2R38 protein (22), are more susceptible to Gram-negative bacterial infection (12), have higher levels of sinonasal bacteria (23,24) and biofilms (25), are at higher risk for chronic rhinosinusitis (26 -29), and may have worse outcomes after endoscopic sinus surgery (30) compared with patients homozygous for the functional (PAV) allele of TAS2R38.…”
mentioning
confidence: 98%
“…Additionally, AVI homozygotes with CRS are more likely to require surgical intervention for medically recalcitrant sinusitis. 55 , 56 , 57 , 58 , 59 , 60 Furthermore, PAV/PAV patients with non-polypoid CRS have better quality of life outcomes 6 months after sinus surgery when compared to heterozygotes and AVI homozygous patients. More recently, genome-wide association tests have identified other less well-studied bitter and sweet receptor genes that are associated with CRS including TAS2R13 and TAS2R49 suggesting that we have only begun to scratch the surface in our understanding of how taste related genes play a role in the pathogenesis of CRS.…”
Section: Introductionmentioning
confidence: 97%
“…A single study that included only 53 patients with chronic rhinosinusitis and 39 healthy controls did not find associations between TAS2R38 genotypes and sinonasal disease 33 . Finally, a study by Cantone et al 34 on 100 subjects confirmed the inverse correlation between TAS2R38 functionality and the risk of developing sinonasal infections caused by gram-negative bacteria. The present study, which included 210 patients with CF and 95 control subjects, confirms that CF patients with both functional alleles of TAS2R38 have a significantly reduced risk of developing to the most severe phase of sinonasal disease, i.e., NP requiring surgery.…”
Section: Discussionmentioning
confidence: 78%